A study of parental involvement in early years: the role of gender and level of education - Hoo, Pui Yin (2024)
This research paper attempted to examine the relationship between parents’ education levels and their involvement in Early Years in Seremban and to investigate whether a significant difference exists between the genders of parents and their involvement in Early Years within the same region. There was limited research investigating the effects and differences of parents’ gender role and educational level on parental involvement in early years. This study applied Epstein’s Model of Six Types of Parent Involvement. Quantitative research method, correlational and cross-sectional research design were applied in this study. Research instrument used in this study was Family Involvement Questionnaire-Short Form (FIQ-SF). Convenience sampling was used, and 62 parents in Seremban with children between the ages of 4 and 6 participated in this study. The finding’s result showed that there was a significant positive relationship between parents’ educational level and home-school conferencing (rho=0.879, p=0.001), school-based involvement (rho=0.883, p=0.001) and home-based involvement (rho=0.891, p=0.001). There was also a significant difference between genders of parents and their involvement in home-school conferencing (p=0.036), but no significant difference in school-based involvement (p=0.130) and home-based involvement (p=0.079). Descriptive analysis revealed that Seremban parents less inclined to participate in school-based activities, implying there was a need to begin intervention programmes to improve collaboration between families and schools. Inferential finding proven that parents’ educational level was significantly positively related to all aspects of parental involvement. Therefore. it alerted the preschools that helping to improve parents’ knowledge and skills to increase parental involvement in school. Additionally, inferential finding indicated that fathers and mother differed in their involvement in home-school conferences. Therefore, it alerted that preschools should pay special attention to encouraging fathers to participate more actively in home-school conferencing. As recommendations, this study suggested implementing average collection strategies, increasing the sample size, and employing random sampling method.